Spatial variation of short birth intervals and their determinant factors among reproductive women in Ethiopia using a geographically weighted regression model - Arega, Gezachew Gebeyehu; Mitku, Aweke Abebaw; Mohammed Hussen, Nuru; Mamaru Awoke, Shegaw; Berelie Berehan, Haymanot; Alem, Kasaneh Jigar (Frontiers in Medicine, 2024)
In low-and middle-income nations, a significant proportion of maternal and infant deaths are caused by a short birth interval (SBI). In Ethiopia, it is the main factor contributing to maternal and infant mortality. Understanding the spatial distribution of short birth intervals, i.e., birth intervals of less than 33 months, and the factors that influence them is important for categorizing and promoting targeted interventions. This study used a geographically weighted regression model to evaluate the factors associated with SBI in hot areas in Ethiopia.The 2019 Ethiopian Mini Demographic and Health Survey, which is nationally representative, provided the data for this study. Enumeration areas made up the first step in the 2-stage cluster design used to collect the data, while households made up the second stage.The survey was conducted between March 21, 2019, and June 28, 2019. Hot spot analysis (local Getis-Ord Gi* statistics) was originally used to investigate spatial variation in short birth intervals. Geographically weighted regression was used to examine the regional variation in the relationship between short birth intervals and the factors that cause them.The results of the study indicated that the overall proportion of short birth intervals of women in Ethiopia was 43.2%. The values for Global Moran's I (Moran's I=0.773 and p < 0.001)) showed the presence of significant SBI clustering in Ethiopian administrative zones in Ethiopia. High-risk areas of the SBI were observed in Jarar, Doolo, Shabelle, Afder, Liben, Korahe, Nogob, West Harerge, Guji, Sidama, and Assosa zones.Living in a geographic region with a high proportion of uneducated women, women lacking breastfeeding practices, and followers of Orthodox religions increased the proportion of short birth intervals. Our full map of hotspots for short birth spacing and the factors that affect them helps in the implementation of precise public health measures for decision-makers.